‘Not-being-at-home’: Subject, Freedom and Transcending in Heideggerian Educational Philosophy - d’Agnese, Vasco (Studies in philosophy and education, 2018)
In my paper, by drawing on the writings Heidegger developed in the late 1920s, I wish to display what we may refer to as the thorough educational nature of Heideggerian reflection. It is my argument that the analysis of Dasein we find in the early Heidegger displays an extraordinary deep and dense reflection on selfhood and subjectivity, a reflection that is rooted in subject’s freedom and transcending. By paying attention to the interplay between these two features, I argue that in the late 1920s, while challenging the notion of an all-encompassing consciousness as the place where everything should be understood and managed, Heidegger built a conception of selfhood and subjectivity in terms of freedom, responsibility, and ongoing transformation. Such a conception, I argue, is in and of itself educational.